Fayzas revertering - Karlsson, Pia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1999)
Within the framework of my PhD-project on religion, gender and cultural change in Swedish mosques I am approaching a field loaded with strong feelings and normative statements. "Muslims" and "Muslim culture" are often regarded as something homogeneous. I would like to nuance this picture by using the concept of discourse to structure thoughts about the process in which a Muslim identity — both ascribed and self-produced — is shaped. For my analysis I take my starting point in a meeting with a young woman, brought up in England by parents of Pakistani origin. Her understanding of Islam has moved from a relatively unreflected one to an intense and reflexive. I argue that her experiences leading to this new expression has been framed and thus directed by a number of discourses, but also that she uses these as a strategy of resistance.